Appcelerator Titanium : patterns and best practices : take your Titanium development experience to the next level, and build your Titanium knowledge on CommonJS structuring, MVC model implementation, memory management, and much more /: patterns and best practices : take your Titanium development experience to the next level, and build your Titanium knowledge on CommonJS structuring, MVC model implementation, memory management, and much more. (2013) - Unknown
No abstract available